2019
DOI: 10.1139/cjpp-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid administration on cardiac tissue matrix metalloproteinase activity and hepatorenal biomarkers in diabetic rats

Abstract: Diabetes mellitus (DM) is a metabolic disorder that causes severe complications. Thus, the aims of this study were to investigate the influence of DM and folic acid treatment on liver and renal biomarkers, and heart remodeling through evaluation of cardiac matrix metalloproteinase (MMP) activity. There were 4 groups: control (physiological saline 1 mL/kg, i.p., 28 days), DM (streptozotocin [STZ] 100 mg/kg in physiological saline, i.p., 1 day), folic acid (FA; 5 mg/kg, i.p., 28 days), and DM+FA (STZ 100 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Treatments caused an increase in organ weights in males, but not in females (Table 3), which may be as a consequence of physiological differences between males and females. These results confirm the findings of (13,27). Mutavdzin et al, 2019 (27), who found that folic acid treatments improve the metabolic status by means of improving liver and kidney functions, and thereby enhancing body homeostasis.…”
Section: Resultssupporting
confidence: 91%
“…Treatments caused an increase in organ weights in males, but not in females (Table 3), which may be as a consequence of physiological differences between males and females. These results confirm the findings of (13,27). Mutavdzin et al, 2019 (27), who found that folic acid treatments improve the metabolic status by means of improving liver and kidney functions, and thereby enhancing body homeostasis.…”
Section: Resultssupporting
confidence: 91%
“…In addition, Bollano et al reported that the protein expression of MMP2 was significantly decreased in the heart tissue of diabetes rat, while MMP9 was unchanged [ 64 ]. However, another study has shown that MMP2 was elevated while MMP9 was decreased in the heart of diabetes rat [ 65 ]. These data indicate that the changing trends of MMP2 and MMP9 are not always the same or similar in diabetes hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have also shown the beneficial effects of folic acid in streptozotocin-induced diabetes mellitus in rats. The results of these studies showed hepato-and cardio-protective effects as well as glycemia reduction in diabetic rats treated with folic acid [95,96]. Folic acid also reduces cardiomyocyte apoptosis in experimentally induced diabetic rats [97].…”
Section: Homocysteine and Diabetesmentioning
confidence: 91%